Modulatory activity of extracellular H(+) and Zn(2+) on ATP-responses at rP2X(1) and rP2X(3) receptors - Wildman, S S (1999)
1. The modulatory activity of extracellular H(+) and Zn(2+) was examined on ATP-responses at rat P2X(1) (rP2X(1)) and rat P2X(3) (rP2X(3)) receptors expressed in Xenopus oocytes and studied under voltage-clamp conditions. 2. Superfused ATP (0.03–30 μM, at pH 7.5) evoked inward currents at rP2X(1) receptors (EC(50) value, 300±7 nM). ATP potency was reduced 2 fold at pH 6.5, and 6 fold at pH 5.5, without altering the maximum ATP effect. Alkaline conditions (pH 8.0) did not alter ATP activity. 3. Superfused ATP (0.01–300 μM, at pH 7.5) evoked inward currents at rP2X(3) receptors (EC(50) value, 1.8±0.3 μM). ATP activity was affected only at pH 5.5, reducing agonist potency 15 fold without altering the maximum ATP effect. 4. Extracellular Zn(2+) inhibited ATP-responses at rP2X(1) receptors in a time-dependent manner, a 20 min pre-incubation being optimal (IC(50) value, 1.0±0.2 μM). However, the Zn(2+) effect was pH-independent, suggesting Zn(2+)- and H(+)-inhibition of ATP-responses occur through independent processes. 5. Extracellular Zn(2+) weakly potentiated ATP-responses at rP2X(3) receptors (EC(50) value, 11±1 μM). The Zn(2+) effect was dependent on pre-incubation time and, with 20 min pre-incubation periods, Zn(2+) potentiated then inhibited ATP-responses in a concentration-dependent, but pH-independent, manner. 6. In summary, ATP activity at rP2X(1) receptors was decreased by both extracellular H(+) and Zn(2+) and their effects were additive. ATP activity at rP2X(3) receptors was less sensitive to H(+)-inhibition and, in contrast, was potentiated by Zn(2+) in a pH-independent manner. These differential effects may help distinguish P2X(1) and P2X(3) receptors in whole tissues.